(untitled) - Janson, H. W. (Englewood Cliffs, New Jersey, 1977)
The title of this book has a dual meaning: it refers both to the events that make the history of art, and to the scholarly discipline that deals with these events. Perhaps it is just as well that the record and its interpretation are thus designated by the same term,...
Keywords: Art; History